Impact of the Covid-19 Pandemic on the Doctor-Patient Relationship: A Qualitative Study in a Tertiary-Care Centre in Lebanon - Abou-Mrad, Tatiana; Haidar, Hazar; Abou-Mrad, Fadi; Arawi, Thalia (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Background: The Covid-19 pandemic imposed numerous constraints on medical practice and exacerbated preexisting vulnerabilities in Lebanon’s healthcare system, which was already grappling with instability due to concurrent political and economic crises. This situation had a complex impact on the doctor-patient relationship (DPR), with both negative and positive repercussions. Methods: We conducted semi-structured interviews with physicians from various specialties practicing at a tertiary-care center in Lebanon. Our study aimed to 1) explore the impact of the Covid-19 pandemic on the DPR in Lebanon, and 2) provide recommendations for improving the DPR, healthcare policy, and education. Results: Thematic analysis of the data revealed that the pandemic had varying effects on the DPR. While both physicians and patients seemed to have developed a more favourable perception of the medical profession, communication between them appeared to be challenged by the use of personal protective equipment and patients’ concerns about close contact with physicians. The media played a vital role in educating and raising awareness during the pandemic but lacked organization and ethical standards, leading to anticipated fear and confusion among the society. Telemedicine emerged as an alternative means for communication and remote care but faced several obstacles including inadequate internet infrastructure and disruptions to physicians’ personal lives. Conclusion: Our qualitative study unveiled the multifaceted impact of the Covid-19 pandemic on perceiving the healthcare system, doctor-patient interactions, and the role of telemedicine in Lebanon, among others. These findings underscore the importance of effective communication in enhancing the DPR, the need to address misinformation on social media, and the imperative for systemic improvements to strengthen the resilience of Lebanon’s healthcare system.